Evaluation of mesophilic Burkholderia sacchari, thermophilic Schlegelella thermodepolymerans and halophilic Halomonas halophila for polyhydroxyalkanoates production on model media mimicking lignocellulose hydrolysates - Kourilova, Xenie; Novackova, Ivana; Koller, Martin; Obruca, Stanislav (Bioresource technology, 2021)
In this work, the mesophilic bacterium Burkholderia sacchari, the halophilic bacterium Halomonas halophila, and the thermophilic bacterium Schlegelella thermodepolymerans were evaluated with regards to their suitability for polyhydroxyalkanoates (PHA) production from model media mimicking lignocellulose hydrolysates. B. sacchari was capable of utilizing all the tested "model hydrolysates", yielding comparable PHA titers and turning out as very robust against lignocellulose-derived microbial inhibitors. On the contrary, H. halophila reached substantially higher PHA titers on hexoses-rich media, while S. thermodepolymerans preferred media rich in pentoses. Both extremophiles were more sensitive to microbial inhibitors than B. sacchari. Nevertheless, considering substantially higher PHA productivity of both extremophiles even in the presence of microbial inhibitors and also other positive factors associated with utilization of extremophiles, such as the reduced risk of microbial contamination, both H. halophila and S. thermodepolymerans are auspicious candidates for sustainable PHA production from abundantly available, inexpensive lignocelluloses.
Keywords: polyhydroxyalkanoáty; Burkholderiaceae; Polyhydroxyalkanoates; Lignocellulose materials; Burkholderia sacchari; Schlegelella thermodepolymerans; Extremophiles; Halomonas; lignin; Lignin; Microbial inhibitors; Comamonadaceae; Halomonas halophila